IMPLEMENTATION OF ECONOMIC OPENNESS AND ITS IMPACT ON HUMAN RESOURCE GROWTH - Havidotinnisa, Siti; Lubis, Fatimah Malini; Lasmiatun , KMT; Olubitan, Joseph Oluremi (PT. Altin Riset Publishing, 2024)
This research aims for implementation openness economy and its impact to growth source Power man . The research method used is qualitative research, qualitative research is a research method used to understand social phenomena in depth. This type of research is literature study research which researchers carry out by collecting, studying and analyzing references or sources obtained by written or written form such as books, journals, articles, documents and other sources of information that are significant to the topic/title being researched. The research results show that openness economy can give encouragement significant to growth source Power man through enhancement access to education , skills , innovation and health . In context this , role policy is very important For ensure that benefit from openness economy can utilized in a way equitable and sustainable for all public . Supportive policies​ investment in education, skills, health, as well strengthening policies​ protection social and reducing inequality economy can help create conducive environment​ for growth source Power inclusive and sustainable humanity.​